Existential territories and Public Health: before and after the pandemic (Research, Society and Development, 2020)
The Communication and Health Information gains enormous relevance in the face of the Covid-19 pandemic and its impacts on the lives of millions of people around the planet, directly or indirectly affected by the action plans adopted in cities, territories, countries and diferent continents. Pandemic statistics reflects an increase in loss of lives as we write this article. Meanwhile, astonished or disorganized, governments are trying to manage information to establish adequate mechanisms to face the pandemic of the new coronavirus, formally enacted by the WHO in March 2020. This article adresses the binomial ‘health communication and information’ as part of health strategies to cope with the pandemic, but it also proposes to examine such strategies based on what is conventionally called the popular mobilization of health surveillance in existential territories, as a concept of a philosophical character.